Sustainable Supply Chain Design in Social at the Macro-Regional Level - I.V. Takmasheva; A. B. Zelinskaya; L.L. Bogomolova (International Journal of Supply Chain Management, 2020)
Abstract- This work is devoted to the study sustainable supply chain in social enterprises activity at the level of the macro-region. To ensure a comprehensive view, a comparative analysis of foreign and domestic research experience in this area was conducted. Special attention was paid to the practice of assessing the level of business development in the Nordic countries. To select indicators for assessing the level of social entrepreneurship in the region, two groups of criteria were formed: requirements for content parameters describing the state and factors of social entrepreneurship, as well as criteria for instrumental parameters that are designed to provide opportunities for quantitative analysis.